Economic evaluation of infrastructures for thermochemical upcycling of post-consumer plastic waste. Issue 3 (3rd January 2023) - Ma, Jiaze; Tominac, Philip A.; Aguirre-Villegas, Horacio A.; Olafasakin, Olumide O.; Wright, Mark M.; Benson, Craig H.; Huber, George W.; Zavala, Victor M.
Abstract : Thermochemical upcycling of post-consumer plastic waste creates a circular economy that is economically viable and that provides environmental benefits. The value chain associated with this economy makes plastic waste a highly valuable feedstock. Abstract : Thermochemical technologies, such as pyrolysis, offer a potentially scalable pathway for upcycling diverse types of plastic waste (PW) into value-added chemicals. However, deploying these technologies in waste management infrastructures is not straightforward because such systems involve a wide range of interdependent stakeholders, processing facilities, and products. In this work, we present a holistic optimization framework that integrates value-chain analysis, techno-economic analysis, and life-cycle analysis for investigating the economic viability and environmental benefits of upcycling infrastructures that collect, sort, clean, and process post-consumer PW for producing virgin polymer resins. The framework is applied to a case study in the upper Midwest region of the US. Our analysis reveals that the infrastructures are economically viable and could activate a regional circular economy that generates over 1 billion USD in annual profit. Moreover, our analysis reveals that this economy can reduce the carbon footprint of PW incineration by half. Our framework also determines the inherent values of post-consumer PW and of derived products such as plastic bales and pyrolysis oil; we find that, in these infrastructures, PW becomes a highly valuable feedstock with a market value of 500 USD per tonne. We discuss how this market value can generate incentives that foster more effective waste pre-sorting practices by consumers that can help bypass material recycling facilities and increase total system profit.